Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1007/bf00666493
|View full text |Cite
|
Sign up to set email alerts
|

Parity is associated with axillary nodal involvement in operable breast cancer

Abstract: In this series, which includes only operatively staged patients, increasing parity is associated with nodal positivity. This effect is of a magnitude similar to that of increasing tumor size, and confirms observations from other studies. Information regarding parity may be useful for prognostic purposes, as well as providing insights into basic breast cancer biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The fi nding that high parity is associated with ALNI is in accordance with three previous studies [6][7][8] . Wohlfahrt et al [9] found in a large Danish cohort that low parity increases risk of ALNI.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The fi nding that high parity is associated with ALNI is in accordance with three previous studies [6][7][8] . Wohlfahrt et al [9] found in a large Danish cohort that low parity increases risk of ALNI.…”
Section: Discussionsupporting
confidence: 80%
“…It is possible to hypothesise that this could promote tumour growth and, hence, increase the frequency of ALNI. Others have suggested that pregnancy induces changes in levels of female sex hormones, which may in turn affect tumour progression and the occurrence of ALNI [7] . This study does not include information in order to confi rm or reject these hypotheses, and these issues will need future attention.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that the postponement of motherhood might have a beneficial effect on overall breast cancer prognosis. Studies on overall parity as a prognostic factor have been contradictory (von Papatestas et al, 1980;Palmer et al, 1982;Black et al, 1983;Wang et al, 1985;Mohle-Boetani et al, 1988; Lees et al, 1989;Mason et al, 1990;Lehrer et al, 1992;Guinee et al, 1994;Korzeniowski and Dyba, 1994;Orr and Fraher, 1995;Schoultz et al, 1995). We have previously found that pregnancy within 2 years before a diagnosis of breast cancer was associated with reduced survival (Kroman et al, 1997).…”
Section: Discussionmentioning
confidence: 99%